E2F transcription factor 1 is involved in the phenotypic modulation of esophageal squamous cell carcinoma cells via microRNA-375 - Pengfei Li (Taylor & Francis Group, 2021)
E2F family of transcription factors modulates multiple cellular functions associated with cell cycle and apoptosis. Here, we focused on the relevance of E2F1 to esophageal squamous cell carcinoma (ESCC) and identification of E2F1-mediated network in this study. Query of Gene Expression Omnibus database revealed that E2F1 was the core gene that was upregulated in ESCC. E2F1 downregulation inhibited ESCC cell activity. microRNA (miR)-375 was confirmed to be a downstream target of E2F1. E2F1 bound to miR-375 promoter and inhibited miR-375 transcription. Moreover, miR-375 inhibitor mitigated the repressive impacts of si-E2F1 on ESCC cells in part. Further study showed that sestrin 3 (SESN3) could interact with miR-375, and its knockdown annulled the stimulative effect of miR-375 inhibitor on ESCC development. Finally, E2F1 and SESN3 downregulation inhibited the phosphatidylinositol 3 kinase (PI3K)/AKT pathway activity in cells, while miR-375 inhibitor promoted PI3K/AKT pathway activation. These findings suggest that E2F1 inhibited miR-375 expression and promoted SESN3 expression to activate the PI3K/AKT pathway in ESCC.